Effects of Extracorporeal Shockwave Therapy on Clinical and Neurophysiological Indices of Spasticity Inpatients With Upper Motor Neuron Lesions: A Systematic Review and Meta-analysis - Ali Reza Akbarzade Bagheban; Farideh Dehghan Manshadi; Nahid Tahan; Fereshteh Poursaeed (University of Social Welfare and Rehabilitation Sciences, 2021)
Objective: Spasticity is one of the components of an Upper Motor Neuron (UMN) lesion that occurs usually after a period of flaccidity in the form of velocity-dependent resistance to passive stretch. Spasticity is a significant cause of limited mobility and disability in neurological diseases. There are several clinical approaches to control spasticity. Recently, Shock Wave Therapy (SWT) has been reported to be a new, safe, and effective method for reducing spasticity for people with upper motor neuron lesions. We conducted a meta-analysis of relevant clinical trials to assess the effect of applying SWT on spasticity in UMN lesions. Materials & Methods: An electronic search was performed in PubMed, ISI Web of Science, Scopus, Science Direct, MEDLINE, and Google scholar from January 2005 to January 2020. Studies were included if they measured spasticity with the Modified Ashworth Scale (MAS) or/and neurophysiological indices in patients with stroke, multiple sclerosis, and cerebral palsy. The keywords of muscle hypertonia or spasticity, extracorporeal shock wave therapy, stroke, multiple sclerosis, and cerebral palsy were used. Two independent researchers searched articles, screened eligible studies against the inclusion criteria, and assessed the methodological quality of included studies. The methodological quality of studies was evaluated using the Downs and Black tool. The difference between the means was considered as the effect size in the MAS and Hoffman reflex/motor response (H/M) ratio before and after the intervention with 95% CI in random-effects models. Analyzes were performed using STATA software version 11. Results: The initial search led to the retrieval of 98 studies based on the inclusion and exclusion criteria, of which 24 full-text articles were reviewed and 14 articles were included in the meta-analysis process. All 14 articles had examined the effects of shockwave on the MAS. Four studies with 120 patients had examined the effects of shockwave therapy on the H/M ratio. Significant reduction in MAS grade was observed immediately [I2 = 100%, P<0.001, SMD=1.38 with 95%CI: (0.80, 1.87)] and three months after SWT [I2 = 100%, P<0.001, SMD=1.13 with 95%CI: (0.50, 1.76)] in comparison with the baseline values. ESWT had no significant effects on the H/M ratio [I2 = 97.5%, P<0.001, SMD=1.09 with 95%CI: (-0.54, 2.73)]. Conclusion: SWT can improve spasticity based on the MAS. The lack of SWT effects on the neurophysiological parameter of spasticity supports this opinion that SWT acts on the non-neural component of spasticity. Differences observed in studies in terms of treatment sessions, intervals of treatment sessions, energy density, number of shocks, and follow-up duration need to be examined more closely. More randomized clinical trials are needed in the future to analyze the impact of these factors on the efficacy of SWT for spastic patients.